Prevalence of Oculo-Visual Disorders amongst University Students in Varanasi District, North India - O.P. Upadhyay, P.R. Sen, R.P. Maurya, Prashant Bhushan, V.P. Singh, M. K. Singh (Pakistan Journal of Ophthalmology, 2012)
Purpose : (a) To estimate the magnitude of various Oculo-visual disorders amongst the University students (b) to find out the factors responsible for the cause of ocular disorders and (c) to suggest possible intervention and preventive strategies for the same. Material and Methods: This Prospective study was conducted in Student Health Care Complex and Department of Ophthalmology, Sir Sundar Lal Hospital, Institute of Medical Sciences of Banaras Hindu University, Varanasi, India. 20,680 students between 15 – 45 years age group were included in this study, which was carried out from September 2009 to August 2010. A detailed clinical history and complete ophthalmic examination of all the students was conducted including best corrected visual acuity, refraction, slit lamp biomicroscopy, Intra Ocular Pressure (IOP) measurement, extra ocular movements and fundus evaluation with direct ophthalmoscope. Clinical details were recorded in a predesigned and pre-tested proforma. After a thorough examination, a provisional ocular diagnosis was made and treatment started accordingly. Result: Out of the 20680 students who visited university students’ health care complex, 4054 had various ocular disorders. The commonest ocular morbidities observed were refractive errors (39.78%) followed by conjunctivitis (30.64%), blepharitis (16.85%), computer vision syndrome (10.73%), stye (8.68%), ocular injuries (8.16%) and others (1.92%). 18.92% students had more than one ocular disorders. Conclusion: Majority of these ocular morbidities need attention as they are preventable and treatable. Hence health education, regular eye checkup and screening are advocated.